Abū al-Mu'īn al-Nasafī (1027–1114 CE) and the Māturīdiyyah School: (A Study of the Concept of Īmān in the Book Al-Tamhīd fī Uṣūl al-Dīn) - Khaerurrazikin Khaerurrazikin (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This research analyzes the concept of Īmān (faith) according to Abū al-Mu'īn al-Nasafī (1027-1114 CE) in his work Al-Tamhīd fī Uṣūl al-Dīn. The study stems from the intellectual unrest and Fitnah that affected the Māturīdiyyah school in Mawarannahr, prompting al-Nasafī to become a key defender of the faith. The study utilizes library research with a descriptive-analytical and qualitative approach, analyzing both primary data from al-Nasafī’s work and secondary theological literature. The findings reveal al-Nasafī's views on Īmān: First, faith is a conviction of truth (Yaqīn) established in the heart towards God. Second, verbal affirmation and actions are symbolic and necessary for Islamic law but do not represent the essence of faith, which lies in the heart. Third, he rejects equating faith with deeds ('Amal), asserting that deeds and conviction are distinct, with conviction being stable and permanent, unlike actions. Al-Nasafī critiques earlier views, like those of al-Raqashī and others, who equated faith with mere verbal affirmation, deeming such views as hypocritical (Nifāq). His approach integrates reason ('Aql) and revelation (Waḥy), employing both Qur'anic texts (Bayānī) and rational arguments (Burhānī) to explain faith.